Re-envisioning Theodore: Theodore of Mopsuestia's biblical exegesis in his "Catechetical homilies" - Puchkova, Sofia ca. 20./21. Jh. (Vigiliae Christianae, 2024)
"Re-envisioning Theodore is the first comprehensive study of Theodore of Mopsuestia's biblical interpretation in his Catechetical Homilies. It challenges the common yet reductionist view of Theodore's exegetical approach as "historical," offering a balanced portrayal of this exegete. Theodore is not a slave of his interpretative methodology, and he may omit the exposition of the historical setting of the Bible and introduce elements not present in the biblical narrative.Re-envisioning Theodore also reveals Theodore's previously little known exegetical ties with Pro-Nicenes and, through them, with Origen. For the first time, this book shows that his exegesis incorporates Greco-Syrian liturgical imagery"--